Energy and the environment in Latin American and Caribbean countries. - Munasinghe, Mohan (1991)
Notes that in the Latin American and Caribbean countries the major energy-related environmental issues include air pollution from electricity generation and transportation, contamination of interior and maritime waters by oil spills, deforestation due to use of wood for fuel, flooding of vast areas by hydraulic dams, and inefficiency in the transformation and use of energy. Points out the need to reconcile development and poverty alleviation goals and responsible management of the environment, considering that such goals will require increased use of energy and raw materials.